SCHOOL CLIMATE AND TEACHER BURNOUT IN THE POST-PANDEMIC TIME - Mortiz, Kristine Joy (International Journal of Arts, Sciences and Education, 2023)
The study investigated the association between school climate and teacher burnout during the post-pandemic period. It involved an investigation into the respondents' characteristics, their perceptions of school climate, and their levels of burnout. The study also looked at how the respondents' characteristics were linked to their levels of burnout, differences in their perceptions of school climate based on their profile, and the connection between their perceptions of school climate and their levels of burnout. Using the descriptive correlational design with 144 public elementary teachers in Sanchez Mira District, the study revealed that in the post-pandemic context, elementary schools in the Sanchez Mira District are perceived as welcoming and supportive environments for both students and educators, resulting in low teacher burnout levels. This low burnout can be attributed to factors such as teachers' length of service and educational attainment. Younger and less experienced teachers, as well as those with higher educational attainment, are more vulnerable to burnout. Importantly, a positive perception of the school environment is associated with reduced levels of burnout among educators, underscoring the significance of fostering positive school climates to enhance teacher well-being and overall education quality.